2022
DOI: 10.3390/md20040258
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Evidence for a Protective Role of Fucoidan from Laminaria japonica in Chronic Kidney Disease-Triggered Cognitive Dysfunction

Abstract: This study aimed to explore the mechanism of fucoidan in chronic kidney disease (CKD)-triggered cognitive dysfunction. The adenine-induced ICR strain CKD mice model was applied, and RNA-Seq was performed for differential gene analysis between aged-CKD and normal mice. As a result, fucoidan (100 and 200 mg kg−1) significantly reversed adenine-induced high expression of urea, uric acid in urine, and creatinine in serum, as well as the novel object recognition memory and spatial memory deficits. RNA sequencing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Fucoidans have shown potential bioactivities, including antioxidant, anti-coagulant, anti-tumor, anti-inflammatory, and management of metabolic diseases and kidney dysfunction [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] with furtherly formulated in pharmaceutical preparations as an essential step for clinical investigations and commercial marketing [ 20 ]. However, the recent studies found that the antioxidant activity is correlated potentially with the phenolic contents in crude fucoidan extracts [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidans have shown potential bioactivities, including antioxidant, anti-coagulant, anti-tumor, anti-inflammatory, and management of metabolic diseases and kidney dysfunction [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] with furtherly formulated in pharmaceutical preparations as an essential step for clinical investigations and commercial marketing [ 20 ]. However, the recent studies found that the antioxidant activity is correlated potentially with the phenolic contents in crude fucoidan extracts [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of CKD, fucoidan has been reported to improve the composition of gut microbiota. , However, there are few reports on the effect of fucoidan on gut microbiota in DN. Herein, we evaluated the effects of fucoidan on intestinal microflora composition in the early stage of DN (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the behavioural changes might be related to changes in hippocampal BDNF and GFAP expression, which are common in renal dysfunction (Ma et al., 2022 ; Mazumder et al., 2019 ). BDNF decrease and GFAP increase could be related to the inflammatory and oxidative changes occurring in hippocampus, as well as urinary Zn losses (Kida et al., 2015 ; Lima Giacobbo et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%